Prenatal Diagnosis of Phrygian Cap Gallbladder: Two- and Three-dimensional Ultrasound, Magnetic Resonance Imaging, and Three-dimensional Reconstructions - Maria Rosa Pereira Martins; Juliana Assis Alves; Mayra Martins Melo; João Victor Jacomele Caldas; Edward Araujo Júnior; Patrícia Soares Oliveira Szejnfeld; Pedro Teixeira Castro; Heron Werner; Liliam Cristine Rolo (Journal of Medical Ultrasound)
A congenital anomaly of the gallbladder called Phrygian cap occurs when an enlarged gallbladder presents a folded shape in the fundus along the body of the organ. The incidence in adults is about 4%. The diagnosis is usually incidental during abdominal imaging for other causes, but prenatal diagnosis of this condition is rare. In this report, two cases of prenatal diagnosis of Phrygian cap were performed using two-(2D) and three-dimensional (3D), magnetic resonance imaging, and 3D reconstructions.